Solid‐Phase Synthesis of Substrate‐Based Dipeptides and Heterocyclic Pseudo‐dipeptides as Potential NO Synthase Inhibitors. (27th February 2020) - Touati‐Jallabe, Youness; Tintillier, Thibault; Mauchauffée, Elodie; Boucher, Jean‐Luc; Leroy, Jérémy; Ramassamy, Booma; Hamzé, Abdallah; Mezghenna, Karima; Bouzekrini, Amine; Verna, Claudia; Martinez, Jean; Lajoix, Anne‐Dominique; et al.
Abstract: More than 160 arginine analogues modified on the C‐terminus via either an amide bond or a heterocyclic moiety (1, 2, 4‐oxadiazole, 1, 3, 4‐oxadiazole and 1, 2, 4‐triazole) were prepared as potential inhibitors of NO synthases (NOS). A methodology involving formation of a thiocitrulline intermediate linked through its side‐chain on a solid support followed by modification of its carboxylate group was developed. Finally, the side‐chain thiourea group was either let unchanged, S ‐alkylated (Me, Et) or guanidinylated (Me, Et) to yield respectively after TFA treatment the corresponding thiocitrulline, S ‐Me/Et‐isothiocitrulline and N ‐Me/Et‐arginine substrate analogues. They all were tested against three recombinant NOS isoforms. Several compounds containing a S ‐Et‐ or a S‐ Me‐Itc moiety and mainly belonging to both the dipeptide‐like and 1, 2, 4‐oxadiazole series were shown to inhibit nNOS and iNOS with IC50 in the 1–50 μM range. Spectral studies confirmed that these new compounds interacted at the heme active site. The more active compounds were found to inhibit intra‐cellular iNOS expressed in RAW264.7 and INS‐1 cells with similar efficiency than the reference compounds L‐NIL and SEIT. Abstract : 164 potential NO synthase inhibitors were prepared on solid support from a single thiocitrulline intermediate anchored by its side chain. Most compounds inhibiting nNOS and/or iNOS with IC50 values in the 1–50 μM range and with selectivity toward eNOS contained an S ‐Et‐Itc moiety and mainly belonged to the dipeptide‐like and 1, 2, 4‐oxadiazole series. Selected inhibitors were found to significantly inhibit iNOS expressed in RAW264.7 and INS‐1 cells.